Self-reflection: A tool to enhance student nurses' authenticity in caring in a clinical setting in South Africa - Lerato Matshaka (Elsevier, 2021)
Background: Self-reflection is a useful tool that can benefit student nurses and patients. It enables the student nurses to develop self-knowledge and awareness of their strengths and weaknesses, and assists them in becoming authentic when providing nursing care to patients. A reflective student nurse is empowered not to dwell on negative experiences and negative thoughts, but to look beyond hurdles and seek positivity and be of value to their patient. Purpose: To determine the impact of self-reflection in enhancing student nurses' authenticity in caring. Design and methods: A quantitative, descriptive, and cross-sectional research design with a purposive sampling method was employed. The researcher obtained ethical clearance from a higher education institution in South Africa, and respondents provided voluntary informed consent for their participation in the study. Respondents were student nurses in their third- and fourth-year level of study. Data were collected through a survey method using a self-administered, standardised, five-facet mindfulness questionnaire. Results: The results showed that 69.74% of student nurses perceived themselves as able to reflect before reacting. The average mean for this facet was (n = 2.93), and the average standard deviation was (n = 0.949). It was determined that 69.74% of the student nurses found the mindfulness facet 'non-reaction to inner experiences' true to them. Conclusions: Student nurses' quality of reflection must be nurtured and cultivated to enhance their caring nature. Reflective learning for student nurses at higher education institutions is recommended to facilitate caring, and self-reflection should be a habitual practice in the clinical area.